Expression of N-cadherin and β-catenin in human meningioma in correlation with peritumoral edema. (2nd September 2018) - Rutkowski, Robert; Chrzanowski, Robert; Trwoga, Magdalena; Kochanowicz, Jan; Turek, Grzegorz; Mariak, Zenon; Reszeć, Joanna
ABSTRACT: Objective : To analyze the expression of β-catenin and N-cadherin in large series of meningioma cases and to investigate their correlation with peritumoral brain edema (PTBE). Materials and methods : Study group consists of 154 patients diagnosed with intracranial meningioma divided into: low-grade (G1) and high-grade (G2 or G3) group. PTBE was graded into four groups (0, I, II, III) using Steinhoff classification. The expression of N-cadherin, β-catenin was analyzed and graded based on the positive ratio of immunoreactivity. The results were analyzed statistically. Results : 104 cases were low-grade and 50 high-grade meningiomas. PTBE was observed in 103(66.8 %) cases: 57 grade I, 44 grade II and 2 grade III. Positive N-cadherin expression was found only in the membrane of the neoplastic cells in 50(48.1%) cases of low-grade, and in 34(68%) of high-grade group. In low-grade meningioma, β-catenin expression was observed within the cytoplasm and nucleus in 54(51.9%) cases. In high-grade meningiomas, β-catenin expression was observed in 33(66%) tumors only within the nucleus. N-cadherin expression was observed in 36 cases with PTBE grade I, 28 with grade II and 2 with grade III. β-catenin expression was observed in 40 cases with PTBE grade I, 24 with grade II and 2 with grade III. The results were statistically significant. Conclusions : Significant N-cadherin expression especially in high-grade meningioma group was found. β-catenin expression was the most evident in the nucleus rather than in cytoplasm. The degree of PTBE correlated with the N-cadherin and β-catenin expression and was the most prominent in high-grade meningioma group.